Advancing Science Education Potential: A Community Outreach Initiative for Teachers at SD Negeri 173637 Narumonda - Candra, Andy; Rahayu, Siti Utari; Marpaung, Tulus Joseph; Erwin (Talenta Publisher, 2025)
In the realm of education, one of the challenges encountered is the limited ability of teachers to utilize science laboratory equipment and create engaging visualizations for classroom learning. This issue adversely affects students' mastery of science concepts. To address this problem, teachers need to use teaching media as aids in the learning process, which is expected to improve student learning outcomes significantly. One proposed medium is using science teaching aids and the Biorender application, which play a critical role in helping students understand the concepts being taught. Students are expected to comprehend the material more efficiently by using teaching aids and modules, reinforcing conceptual mastery, developing skills, and increasing their learning interests. The methods used in this activity included lectures and practical tutorials, where teachers were introduced to the use of science teaching aids and the application of Biorender to create engaging visualizations for classroom teaching. After participating in this activity, SD Negeri 173637 Narumonda teachers gained additional knowledge. They acquired new skills in using science teaching aids and the Biorender application. This enables them to implement more engaging and effective teaching techniques in science lessons, improving students' understanding and interest in learning.